"If you can have one glass of wine now and then, why are you denying that to a woman with no evidence": Knowledge and practices of health professionals concerning alcohol consumption during pregnancy. Issue 4 (December 2015) - Crawford-Williams, Fiona; Steen, Mary; Esterman, Adrian; Fielder, Andrea; Mikocka-Walus, Antonina
Abstract: Background: Alcohol consumption during pregnancy has the potential to cause significant harm to the foetus and the current Australian guidelines state that it is safest not to drink alcohol while pregnant. However, conflicting messages often appear in the media and it is unclear if the message to avoid alcohol is being effectively conveyed to pregnant women. Aims: This research aims to explore the advice that health professionals provide to pregnant women about alcohol consumption; the knowledge of health professionals regarding the effects of alcohol consumption; and their consistency with following the Australian guidelines. Methods: Ten semi-structured face to face interviews were conducted with health professionals who regularly provide antenatal care. These include midwives, obstetricians, and shared care general practitioners. A six-stage thematic analysis framework was used to analyse the interview data in a systematic way to ensure rigour and transparency. The analysis involved coding data extracts, followed by identifying the major themes. Findings: Health professionals displayed adequate knowledge that alcohol can cause physical and mental difficulties that are lifelong; however, knowledge of the term FASD and the broad spectrum of difficulties associated with alcohol consumption during pregnancy was limited. Although health professionals were willing to discuss alcohol with pregnant women, many did not make this a routine part of practice, and several concerning judgements were noted. Conclusion: Communication between health professionals and pregnant women needs to be improved to ensure that accurate information about alcohol use in pregnancy is being provided. Further, it is important to ensure that the national guidelines are being supported by health professionals.